Historicity, realism and truth (2017)
This paper argues that the historical character of our knowledge is compatible with both ontological and epistemological realism. The first part critically analyses the thesis according to which the situated nature of our cognitive practices implies that they do not refer to an extra-linguistic reality. The second section explores the claim that realism is a necessary presupposition of our communicative practices and the final part outlines the principles of a pluralist realism.